Enhancing last Mile Connectivity Through Inclusive Planning A case of Namma Metro, Bengaluru Master - Das, Bipasha (SPA Bhopal, 2024)
“An advanced city is not one where even the poor use cars, but rather one where even the rich use public transport”, Enrique Penalosa, 2013. The need for sustainable solutions is of prime importance, as the demand for better infrastructure increases with rapid urbanization and conventional planning methods struggle to keep pace. A paradigm shift is required towards inclusive, citizen centric planning, where public participation transcends mere formality and becomes a cornerstone for creating equitable co-producing cities. This imperative extends to mobility planning, where traditional practices succumb to sustainable smart mobility solutions aimed at reducing congestion, emissions, etc. Furthermore, dynamic cities demand more than just technocratic advocacy that necessitates the integration of planning, governance, technology, and active citizen participation to achieve this vision. This research focuses specifically on designing a participatory framework for enhancing last mile connectivity for the metro, a critical factor in optimizing the expanding metro system and achieving sustainable mobility goals in Bengaluru, one of India's largest and fastest growing global metropolises. The riders are acknowledged as the co-creators and co producers of the metro system, which needs to be realized to optimum potential to enable them to bridge the gap between envisioned planning on paper and it’s on ground execution. The research primarily focuses on four objectives. Informed by existing models of collaboration between government agencies, end users, and civil societies in sustainable mobility, the various categories of participatory tools present for sustaining a service are identified along with the scale of collaboration and type of interaction practiced. Secondly, is to evaluate the functioning of governance in Bengaluru that addresses last mile connectivity. The research will identify factors affecting last mile connectivity, analyze the role of supporting actors in bridging the gap between policy intent and implementation, and explore the scope of participatory mechanisms for enhancing last mile connectivity. Thirdly, the research evaluates the effectiveness of governance in addressing last mile connectivity challenges, by studying the nature & extent of partnership between civil societies, end users & government agencies for last mile connectivity, which shall be investigated through various categories of participatory tools present, the scale and type of interaction required. The objective is to assess the government's approach through elements like equity, spatial justice, and collaborative planning and analyze their impact on metro ridership and the range of users benefitted. The research shall be conducted through qualitative methodology and the findings shall be validated through existing quantitative data conducted by relevant organizations to understand the participatory transport planning process (PTPP) in Bengaluru. Diverse data collection methods shall be employed including key informant surveys that will lastly, inform the proposed framework outlining optimal forms of engagement in the context of Bengaluru’s mobility planning and hold the potential to be generalized to enhance last mile connectivity throughout the metro system, contributing to a more inclusive, sustainable, and citizen centric urban mobility landscape.
Keywords: Public Participation; Transport Planning; Sustainable Mobility